Lease Common Money under the Palestinian Legislation : A Comparative Study - Hussain, Ashraf (Journal of Legal Sciences, 2023)
The study aimed to shed light on the provisions of the lease of the common money as a whole or the common share, these provisions still raise problems when applied, and the fact is that the lease contract concluded by all or one of the partners with others is based on the exchange of a clear benefit, which is the exploitation of the real estate that is a circle between these partners Considering that they are one person in the eyes of the law and he is the landlord or by one of their partners, the researcher compared the texts of the articles of the Journal of Justice Rulings - from which most of the rulings were derived because they are applied in Palestine - with the texts of the Egyptian Civil Code No. 131 of 1948; This is to make a brief and clear elaboration between these two laws, which differ in their presentation of the subject and their treatment of the provisions. The descriptive analytical approach was used for the purposes of achieving the objectives of the study. Their right to benefit from it, and if these actions were carried out by one partner, he did not need the approval of the partners, and the partner was like an agent on their behalf, and if it happened and if they objected to it, it is considered invalid and not implemented, and these actions may be material actions and may be legal actions. The study recommended a set of recommendations The most prominent of which is the need to work on enacting new legislation that deals with all the provisions and rules of joint ownership, and is based on regulating all forms of this ownership, its provisions, and the rules for its division among partners.